Pengembangan E-LKPD Berbasis Realistic Mathematics Education pada Materi Barisan dan Deret. - Gustiani Putri; Anna Cesaria; Dewi Yuliana Fitri (RANGE: Jurnal Pendidikan Matematika, 2023)
The purpose of this research is to develop a valid and practical E-LKPD based on Realistic Mathematics Education at SMAN 2 Koto Baru Dharmasraya. This type of research is research development (Research & Development). The development model used is the Plomp development model. The stages used in this development model only reached the second stage, namely the preliminary research and prototyping phase. The instruments used in this study were validity questionnaires, practicality questionnaires and interview guidelines. Based on the results of data analysis, it was found that the RME-based E-LKPD developed obtained an E-LKPD validity of 80.486% with a very valid category. The final practicality score that obtained the E-LKPD practicality result was 82.832% with a very valid category. Based on the results of the study, it can be concluded that the RME-based E-LKPD on sequences and series material at SMAN 2 Koto Baru Dharmasraya is stated to be valid and practical for use by educators and students in learning activities.